Exploring the potential of topsoil pellets to improve native seedling establishment on degraded agricultural land - Thomas P. Munro; Todd E. Erickson; Dale G. Nimmo; Frederick A. Dadzie; Miriam Muñoz-Rojas; Jodi N. Price (Plant and Soil, 2024)
Background and aims Agricultural activities can degrade soils and promote weeds, posing challenges to native species restoration. In agricultural restoration, removing contaminated topsoil is a method designed to reduce elevated soil nutrients caused by fertilisation. This strategy targets weed control by eliminating both aboveground weeds and their soil seed bank before direct seeding. However, it also diminishes native soil seed banks and beneficial soil microbes. We investigated the potential of fresh topsoil pellets containing seeds to improve seedling performance in a degraded grassy woodland where topsoil had been removed. Methods We tested various pellet recipes, including one using commercial ingredients and three with different topsoil proportions (30%, 50%, and 70%). The study was conducted in a degraded grassy woodland in southeastern Australia, where topsoil was removed for restoration. We explored the effect of these pellet varieties on seedling emergence and growth of six native species common in this community, as well as microbial activity in the soil surrounding the seedlings. Results Pellets significantly improved the emergence of Chrysocephalum apiculatum , providing evidence of their effectiveness. However, pellets significantly reduced Arthropodium milleflorum and Glycine tabacina emergence. Linum marginale and Rytidosperma caespitosum emergence remained unaffected by pellets . One species, Bothriochloa macra, had insufficient emergence for analysis. The microbial activity of the soil surrounding Rytidosperma caespitosum seedlings was significantly improved by pellets, with no significant effects observed for other species. Conclusion Our results demonstrate that topsoil pellets improved the emergence of one native species, but reduced emergence for two others, indicating species-specific responses to pelleting.